(untitled) (Colombia Medica, 1994)
The study seeks to determine the factors readily identifiable by non-medical healthcare workers that, at the time of an episode of acute respiratory infection (ARI), serve to define when it is an episode of low acute respiratory infection (LRTI). The study was conducted in Cali, Colombia, in a cohort of children from birth to 48 months. A total of 3,268 episodes of ARI were identified, of which 1,000 corresponded to episodes of low ARF